PHT427 as an effective New Delhi metallo-β-lactamase-1 (NDM-1) inhibitor restored the susceptibility of meropenem against Enterobacteriaceae producing NDM-1 - Li, Xiaohui; Wang, Qian; Zheng, Ji; Guan, Yan; Liu, Chennan; Han, Jiangxue; Liu, Sihan; Liu, Tianjun; Xiao, Chunling; Wang, Xiao; Liu, Yishuang (Frontiers in Microbiology, 2023)
With the increasingly serious problem of bacterial drug resistance caused by NDM-1, it is an important strategy to find effective inhibitors to assist β-lactamase antibiotic treatment against NDM-1 resistant bacteria. In this study, we identified a hit compound PHT427 which could significantly inhibit the activity of NDM-1 through high-throughput screening, with an IC50 of 1.42 μmol/L. PHT427 restored the susceptibility of meropenem against E.coli BL21(DE3)/pET30a(+)-blaNDM-1 and Klebsiella pneumoniae clinical strain C1928 (producing NDM-1) in vitro. The interaction between PHT427 and NDM-1 was confirmed by fluorescence quenching and surface plasmon resonance (SPR) assays. In addition, molecular docking results indicated that PHT427 could act on the zinc ions at the active site of NDM-1 and the catalytic key amino acid residues simultaneously. The mutation of Asn220 and Gln123 abolished the affinity of NDM-1 by PHT427 via SPR assay. Moreover, PHT427 showed low cytotoxicity in vitro. In conclusion, our data demonstrate that PHT427 is a promising lead compound against carbapenem-resistant bacteria.